Analyse des performances bouchères de la population ovine exploitée dans wilaya de Tébessa - Douaa,Djebbari (My University, 2023)
The assessment of the butchering performances in sheep, allowed us to approach the structure of this population intended for slaughter and consumption; to determine the main characteristics according to âge, sex, breed, measurements, live weights, carcass weight and yield. This study was carried out on a total of 7 ewes and 138 rams (february – april, 2023) at the municipal slaughterhouse in the wilaya of Tébessa on sheep belonged to two breeds (Ouled-Djellal and Hamra). The results obtained for the butcher parameters in the two breeds are respectively: chest circumference (1.04±0.09 and 1.02±0.09)m;; scapulo-ischial length (79.26±10.08 and 81.60±9.94)cm; the width at the pelvis (38.66±4.83 and 39.10± 4.94) cm, leg length (43.81±3.57 and 44.93±6.15) cm; carcass length (75.72±9.35 and 74.13±6.55) cm; chest width (45.95±5.09 and 45.98±3.58) cm ; shoulder width(44.25±5.24 and 44.46±3.26) cm; fat condition (1.57 ± 1.04 and 1.47±1.01) mm;weight of carcasses(34.48±9.56 and 33.23±6.68)kg; weight of feet (1.48±0.5 and 1.32±0.28)kg;head weight(4.09±2.57 and 3.67±0.86) kg; weight of offal(16.69±2.96 and 16.31±2.40)kg; live weight(92.69±24.73 and 86.93 ±22.02)kg. The sheep of the Ouled-Djellal breed âged more than 2 years are the heaviest; they have a very wide chest, a thick frame, a very long carcass. The yield varies according to the breed of the animals in a non-significant way (p> 0.05), it is 39.15% and 38.47% respectively for the Ouled-Djellal breed and Hamra breed. This work has also made it possible to detect the excellent meat performances of a category of animals and to propose ways of improving these breeds whose qualities of adaptability and hardiness are no longer to be demonstrated...................... سمح لنا تقييم أداء معلمات الجزار في الأغنام بالاقتراب من هيكل هذه المجموعة المخصصة للذبح والاستهلاك. تحديد الخصائص الرئيسية حسب العمر والجنس والسلالة والقياسات والوزن الحي ووزن الذبيحة والعائد. أجريت هذه الدراسة على ما مجموعه 7 نعاج و 138 كبش (فيفري –أفريل2023 ) في المسلخ البلدي لولاية تبسة على أغنام تنتمي إلى سلالتين (أولاد جلال و الحمرا). النتائج التي تم الحصول عليها لمعلمات الجزار في السلالتين هي على التوالي: محيط الصدر (1.04±0.09 و 1.02±0.09) م; الطول الكلي10.08±79.26) و 81.60±9.94) سم ؛ عرض الحوض (38.66±4.83 و 39.10±4.94) سم ، طول الساق (43.81±3.57 و 44.93±6.15) سم ؛ طول الذبيحة (75.72±9.35 و 74.13±6.55) سم ؛ عرض الصدر (45.95±5.09 و 45.98±3.58) سم ؛ عرض الكتف (44.25±5.24 و 44.46±3.26) سم ؛سمك الدهون (1.57 ± 1.04 و 1.47±1.01) ملم ;وزن الذبيحة (34.48±9.56 و 33.23±6.68) كغ ؛ وزن الاقدام (1.48±0.5 و 1.32±0.28) كغ ;وزن الرأس (4.09±2.57 و 3.67±0.86) كغ ؛ ;وزن الزوائد (16.69±2.96 و 16.31±2.40) كغ ;الوزن الحي المحسوب (92.69±24.73 و 86.93 ±22.02) كغ. الأغنام من سلالة أولاد جلال الذين تتراوح أعمارهم بين أكثر من 2 سنوات هي الأثقل، لديهم الصدر العميق واسعة جدا، إطار سميك، الذبيحة و الساق طويلة جدا. يختلف المحصول حسب سلالة الحيوانات بطريقة غير مهمة (ع> 0.05) ، فهو 39.15 ٪ ، 38.47 ٪ على التوالي لسلالة أولاد جلال وسلالة الحمرا. وقد أتاح هذا العمل أيضا اكتشاف أداء اللحوم الممتاز لفئة من الحيوانات واقتراح طرق لتحسين هذه السلالات التي لم يعد من الممكن إثبات صفاتها من القدرة على التكيف والصلابة.......................... L’appréciation des performances bouchères chez les ovins, nous a permis une approche de la structure de cette population destinée à l’abattage et à la consommation ; de déterminer les principales caractéristiques en fonction de l’âge, du sexe, race, mensurations, poids vifs, poids de la carcasse et rendement. Cette étude a été effectuée sur une totale de 7 brebis et 138 moutons (février – avril, 2023) à l’abattoir municipale de la wilaya de Tébessa sur des ovins appartenant à deux races (Ouled-Djellal et Hamra). Les résultats obtenus chez les deux races (Ouled-Djellal et Hamra) respectivement sont : le tour de poitrine (1,04±0,09 et 1,02±0 ,09) m ; la longueur scapulo ischiale (79,26±10,08et 81,60±9,94)cm ; la largeur au bassin (38,66±4,83 et 39,10±4,94) cm, la longueur de gigot (43,81±3,57 et 44,93±6,15) cm ; la longueur de carcasse (75,72±9,35 et 74,13±6,55) cm ; largeur aux thorax (45,95±5,09 et 45,98±3,58) cm ; la largeur aux épaules(44,25±5,24 et 44,46±3,26) cm ;état de graisse (1,57 ± 1,04 et 1,47±1,01) mm ;le poids de carcasses(34,48±9,56 et 33,23±6,68)kg ; poids de pieds (1,48±0,5 et 1,32±0,28)kg ; poids de tête(4,09±2,57 et 3,67±0,86) kg ; le poids des abats(16,69±2,96 et 16,31±2,40)kg ;poids vif (92,69±24,73 et 86,93 ±22,02) kg. Les ovins de la race Ouled-Djellal âgés plus de 2 ans sont les plus lourds, ils ont une poitrine profondeet un gigot très longs. Le rendement varie en fonction de la race des animaux d’une manière non significative (p>0,05), il est de 39,15%, et 38,47 % respectivement pour la race Ouled-Djellal et race Hamra. Ce travail a permis en outre de déceler les excellentes performances viande d’une catégorie d’animaux et de proposer les voies d’amélioration de ces races dont les qualités d’adaptabilité et de rusticité ne sont plus à démontrer.